Horrible harry and the holidaze eaudiobook - Kline, Suzy (Horrible Harry, 2006)
Suzy Kline, popular children's book author, adds another fun-filled classroom episode to her Horrible Harry series. The holidays are swiftly approaching, and this year in Room 3B the children discover that Christmas is not the only celebration that occurs at this magical time of year. Everyone is excited, except for Harry, who not only seems uninterested in the holidays, but has just plain stopped being horrible! Can Doug find out what is causing his holiday daze?